ANALISIS DAMPAK PERMEN KP RI NOMOR 1/PERMEN-KP/2015 TERHADAP PERDAGANGAN DOMESTIK ANTAR PROVINSI KOMODITI LOBSTER (Panulirus spp), KEPITING (Scylla serrata) DAN RAJUNGAN (Portunus pelagicus) DI KALIMANTAN SELATAN - Ichi Langlang Buana Machmud; Idiannor Mahyudin; Emmy Lilimantik (EnviroScienteae, 2017)
This study aims to (1) analyze the impact of Permen KP RI No. 1/PERMEN-KP/2015 against the decrease/increase of the amount of volume, frequency and value of interprovincial domestic trade of lobster (Panulirus spp), crab (Scylla serrata) and small crab (Portunus pelagicus) commodities; (2) to analyze the causes of the offense of smuggling attempts by large inter-provincial traders of lobster (Panulirus spp), crab (Scylla serrata) and small crab (Portunus pelagicus) commodities; and (3) to analyze the impact of Permen KP RI No.1/PERMEN-KP/2015 against the marketing channels of trade of lobster (Panulirus spp), crab (Scylla serrata) and small crab (Portunus pelagicus) commodities and trade organizations involved in domestic trade of the three commodities.  This thesis study activities were carried out in the province of South Kalimantan. The data collected were data sourced directly from the observation in the study site, and other supporting data relating to the object of study.  The results of this study: (1) Impact of Permen KP RI No. 1/PERMEN-KP/2015 are as follows: (a) it has an effect of significantly reducing the volume, frequency and value of inter-provincial domestic trade of live crab (Scylla serrata) and small fresh crab (Portunus pelagicus) commodities, (b) it has an effect of significantly reducing the volume and value of trade and has no significant effect on the frequency of inter-provincial domestic trade of soft-shelled crab commodity (Scylla serrata); (c) it has no impact on inter-provincial domestic trade of fresh/frozen lobster commodities (Panulirus spp); (d) it has no significant effect on the volume, frequency and value of inter-provincial domestic trade of crab meat (Scylla serrata), small crab meat (Portunus pelagicus), fresh/boiled crab (Scylla serrata) and live lobsters (Panulirus spp) commodities. (2) The occurrence of repeated violations in the form of an attempt smuggling by entrepreneurs (wholesalers) of inter-provincial domestic sender of crab (Scylla serrata) and small crab (Portunus pelagicus) in South Kalimantan caused by less strict actions and sanctions in accordance with applicable laws and regulations as well as the background of route system purchase (overall purchase) in the marketing chain. (3) Permen KP RI No. 1/PERMEN-KP/2015 affects on the forming of a new pattern of marketing chart and new institution in commodities trading of live crab (Scylla serrata), soft-shelled crabs (Scylla serrata) and small fresh crab (Portunus pelagicus) after the application of these rules.